Evaluation of the Quality Family Village Program in Juhut Village, Karang Tanjung District, Pandeglang Regency - Az-Zahra, Zulfa (NIAGARA Scientific Journal, 2024)
The Indonesian government has launched the Family Planning (KB) Program as a strategic step to overcome various population challenges. This program is designed with the main objective of suppressing the population growth rate, as well as improving the quality of life of mothers and children. In its implementation, there are several problems related to the evaluation of the Quality Family Village Program in Canggoang Village, Juhut District, Pandeglang Regency, which resulted in suboptimal program achievements such as low levels of education, lack of health services, including family planning and reproductive health, and lack of community participation in KB Village activities. This study aims to determine the Evaluation of the Quality Family Village Program in Canggoang Village, Karang Tanjung District, Pandeglang Regency. The theory used is William N Dunn's theory. This study uses a descriptive qualitative method. Data collection techniques used are interviews, observations and documentation. The results of the study indicate that the implementation of the evaluation that has been carried out in the Quality Family Village Program in Canggoang Village, Juhut Village, Karang Tanjung District, Pandeglang Regency, it can be concluded that this program has generally succeeded in achieving its stated objectives. This program has given positive impacts in various aspects, such as improving the quality of life of the community, increasing health awareness, and developing human resources.